(untitled) (Proceedings of the World Disability & Rehabilitation Conference, 2019)
Spinal cord injury (SCI) has high mortality and morbidity. Prevention is the best way to reduce the burden on health sector and society. Lack of a large scale referral study on epidemiology of SCI in Sri Lanka, is a barrier to improve methods of prevention. A descriptive (prospective) study was conducted in Rheumatology and Rehabilitation Hospital, Ragama, where randomly selected 42 patients diagnosed of traumatic spinal injuries were presented with an interviewer-administered questionnaire after consent. Mean age of the study population was 32.74 years (SD 11.94), where 86.36% of them were males. 61.9% were married. 85.7% were occupied, out of which the majority had engaged in elementary occupations (33.34%). Only 28.6% had secondary or higher education. Most of the injuries (44.4%) were due to falls occurred during occupational activities. Other significant etiologies contributed include falls during recreational / house hold activities and road traffic accidents with 22.7% and 22.2% respectively. Interestingly 78.94% of the injuries occurred during weekdays while 47.37% of the injuries took place during routine working hours (8.00 am to 4.00 pm). The majority had thoracic spinal injuries (55.56%), while 33.2% and 11.2% had cervical and lumbosacral injuries respectively. 52.4% had severe presentation with complete ASIA (American Spinal Injury Association) level “A” injuries. The final analysis indicates that traumatic SCI are more common among young males with low level of education, who engaged in elementary occupations. Hence these populations should be mainly targeted when planning methods of SCI prevention in Sri Lanka.